Exploring teacher performance: a review of concepts and approaches - Azeem, Nazia; Omar, Muhd Khaizer (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Professional teachers’ competency is helpful in making teaching method more effective and successful which helps the learner to improve their learning abilities, enhance their knowledge and polish their skills. Assessment of teachers’ performance is necessary to determine the competency of teachers’ and it is not a straight forward attempt by solely examining students’ academic achievement. Therefore, this conceptual paper intends to review the literature in order to gain clearer perception about the concept of teachers’ performance assessment. In order to develop our understanding about the teachers’ performance assessment we have created various questions. Specifically, the conceptual paper asks questions: What is meant by teacher performance and teachers’ performance assessment? And: What are approaches of teachers’ performances? This paper is a reference-based study in which information and data was assembled from journal articles, conferences proceedings, books, as well as theses and dissertations. This paper will serve as a basis for future study to develop an instrument that is hoped to measure teachers’ instructional performance. Furthermore, it will extend knowledge on the concept and approaches to teachers’ performance assessment.